Assessment of the Implication of Government Restrictions of Social Media on Freedom of Expression in Nigeria - Ekpah, Mimidoo; Dagba, Bem Joshua; Hiim, Ngufan (Kashere Journal of Politics and International Relations, 2024)
This study, “Assessment of the implication of government restrictions of social media on freedom of expression” sought to determine the nature of government restriction of social media, establish audience reaction towards government restrictions of social media on freedom of expression. The study was solely anchored on the authoritarian media theory. Using the survey research method, a sample size of 384 respondents were reached using the questionnaire instrument. Notably too, data gathered were analyzed using simple percentages. Findings revealed that there are different forms of government restrictions of social media such as content censorship, social media taxation, user registration and partial or complete ban. Findings further indicated that government restriction of social media impede freedom of expression to a very high extent. The study concluded that government restriction of social media impedes freedom of expression to a very high extent. The study recommended that government at all levels should discontinue from enforcing any of the forms of social media restrictions.